Evolution, not transgenerational plasticity, explains the adaptive divergence of acorn ant thermal tolerance across an urban–rural temperature cline. (18th July 2019) - Martin, Ryan A.; Chick, Lacy D.; Yilmaz, Aaron R.; Diamond, Sarah E.
Abstract: Although studies increasingly disentangle phenotypic plasticity from evolutionary responses to environmental change, few test for transgenerational plasticity in this context. Here, we evaluate whether phenotypic divergence of acorn ants in response to urbanization is driven by transgenerational plasticity rather than evolution. F2 generation worker ants (offspring of laboratory‐born queens) exhibited similar divergence among urban and rural populations as field‐born worker ants, suggesting that evolutionary divergence rather than transgenerational plasticity was primarily responsible for shifts toward higher heat tolerance and diminished cold tolerance in urban acorn ants. Hybrid offspring from matings between urban and rural populations also indicated that evolutionary divergence was likely the primary mechanism underlying population differences in thermal tolerance. Specifically, thermal tolerance traits were not inherited either maternally or paternally in the hybrid pairings as would be expected for strong parental or grandparental effects mediated through a single sex. Urban–rural hybrid offspring provided further insight into the genetic architecture of thermal adaptation. Heat tolerance of hybrids more resembled the urban–urban pure type, whereas cold tolerance of hybrids more resembled the rural–rural pure type. As a consequence, thermal tolerance traits in this system appear to be influenced by dominance rather than being purely additive traits, and heat and cold tolerance might be determined by separate genes. Though transgenerational plasticity does not appear to explain divergence of acorn ant thermal tolerance, its role in divergence of other traits and across other urbanization gradients merits further study.